2019
DOI: 10.1155/2019/9198506
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features, Risk Factors, and Outcome of Aneurysmal Lesions in Behcet’s Disease

Abstract: Objective. To investigate the clinical features and potential risk factors of aneurysmal lesions in Behcet’s disease (BD). Methods. We retrospectively reviewed the clinical data of BD patients with aneurysmal lesions in our institute from 1997 to 2017 and compared them with 207 BD patients without aneurysmal lesions. The treatment and outcome of these patients were also analyzed. Results. Sixty-nine patients were included with 117 aneurysmal lesions. The average period between BD onset and diagnosis of aneurys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A retrospective study from China in 2019 showed that development of aneurysms happens in the early stages of treatment naïve male BD patients, and new oral/ genital lesions or pathergy reactions can be independent risk factors for aneurysm development [9]. Interestingly it has been reported that BD patients with pulmonary artery aneurysms usually present with haemoptysis, which was not observed in our patient [9,10].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A retrospective study from China in 2019 showed that development of aneurysms happens in the early stages of treatment naïve male BD patients, and new oral/ genital lesions or pathergy reactions can be independent risk factors for aneurysm development [9]. Interestingly it has been reported that BD patients with pulmonary artery aneurysms usually present with haemoptysis, which was not observed in our patient [9,10].…”
Section: Discussionmentioning
confidence: 53%
“…Given the complexity of disease and varied presentation, patients with BD have poor prognosis if aneurysmal lesions are identified, with pulmonary aneurysm being the most common fatal complication in men [8]. A retrospective study from China in 2019 showed that development of aneurysms happens in the early stages of treatment naïve male BD patients, and new oral/ genital lesions or pathergy reactions can be independent risk factors for aneurysm development [9]. Interestingly it has been reported that BD patients with pulmonary artery aneurysms usually present with haemoptysis, which was not observed in our patient [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Combined with aneurysm rupture, especially pulmonary aneurysm rupture, significantly increased the risk of death in BD patients ( 34 ). Pathergy, arterial occlusion, arterial stenosis, and arterial thrombosis are risk factors for aneurysm formation ( 35 ). The incidence of pseudoaneurysms is higher than that of true aneurysms in BD patients, and pseudoaneurysms are more likely to rupture ( 36 ), the formation of which is related to traumatic artery operation ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though relatively rare in the complications of BD, 21 aneurysmal lesions are associated with high mortality due to the high risk of rupture. Zhou et al 22 found the development of aneurysmal lesions tended to occur in the early phase of BD and develop at abdominal aorta. In this study, most BAPs (58.8%, 10/17) were also observed to be sited at abdominal aorta.…”
Section: Discussionmentioning
confidence: 99%